2017
DOI: 10.1097/inf.0000000000001570
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset Sepsis in Extremely Premature Infants

Abstract: Background Late-onset sepsis (LOS) is an important cause of death and neurodevelopmental impairment in premature infants. The purpose of this study was to assess overall incidence of LOS, distribution of LOS-causative organisms, and center variation in incidence of LOS for extremely premature infants over time. Methods In a retrospective analysis of infants 401–1000 g birth weight and 22–28 6/7 weeks’ gestational age born at 12 NICHD Neonatal Research Network centers in the years 2000–2005 (Era 1) or 2006–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 28 publications
(34 reference statements)
7
103
1
2
Order By: Relevance
“…The idea that clinicians should rely more on correctly drawn blood cultures to confirm infection, rather than decide to continue treatment according to the results of inflammatory markers, has also gained traction, with many advocating a reduction in the diagnosis of culture-negative sepsis. 18,104,105 In our opinion, there are many interesting strategies that require further investigation (see Table 2). With established evidence for the use of Pct-guided antibiotic stewardship, 45 this strategy should be considered to limit the ongoing treatment of culture-negative sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The idea that clinicians should rely more on correctly drawn blood cultures to confirm infection, rather than decide to continue treatment according to the results of inflammatory markers, has also gained traction, with many advocating a reduction in the diagnosis of culture-negative sepsis. 18,104,105 In our opinion, there are many interesting strategies that require further investigation (see Table 2). With established evidence for the use of Pct-guided antibiotic stewardship, 45 this strategy should be considered to limit the ongoing treatment of culture-negative sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Culture-confirmed EOS occurs in ~1% of VLBW infants, an incidence that is 20-fold higher than that in infants born with birth weight >2500 g 17. Culture-confirmed LOS is reported in ~20% of ELBW infants 18. Additionally, 5% of overall mortality in the ELBW population is attributable to infection and NEC 19.…”
Section: Risks and Benefits Of Antibiotics For Preterm Infantsmentioning
confidence: 99%
“…In addition, screening of bodily fluids (e.g., blood and urine) may also require an invasive procedure, increasing the risk for LOS independently [6]. Several studies have identified risk factors for LOS, including a lower birth weight, gestational age (GA), and the presence of central venous catheters [1, 3, 7]. In addition, breastmilk feeding within the first month of life has been shown to be protective against LOS development [8].…”
Section: Introductionmentioning
confidence: 99%